Increase the attractiveness of local fruits to buying intention of hedonic consumers in bali - Korry, Putu Dyah Permatha; Yulianti, Ni Made Dhian Rani; Yunita, Putu Irma (International research journal of management, IT and social sciences, 2017)
In order to improve the competitiveness of local fruits in Bali in particular and Indonesia in general against imported fruits, especially for hedonic consumers, appropriate strategies and policies are needed in the development and strengthening of the market. So the purpose of this research was: 1). To know the influence of labeling to the buying intention of local fruit on hedonic consumers in Bali. 2) To know the influence of brand image to consumer buying intention of local fruit on hedonic consumers in Bali. 3). To know the influence of packaging on the buying intention of local fruit on the hedonic consumer in Bali. This research was conducted on local and imported fruit consumers in Bali. The research location is in fruit shops, supermarkets and traditional markets that sell local and imported fruits in Bali Province. This data is obtained by using a survey method, that is by distributing questionnaires to the respondents.